Assessment of a multi-modal intervention for the prevention of catheter-associated urinary tract infections. Issue 2 (October 2016) - Ternavasio-de la Vega, H.G.; Barbosa Ventura, A.; Castaño-Romero, F.; Sauchelli, F.D.; Prolo Acosta, A.; Rodríguez Alcázar, F.J.; Vicente Sánchez, A.; Ruiz Antúnez, E.; Marcos, M.; Laso, J.
Summary: Background: Catheter-associated urinary tract infections (CAUTIs) represent an important healthcare burden. Aim: To assess the effectiveness of an evidence-based multi-modal, multi-disciplinary intervention intended to improve outcomes by reducing the use of urinary catheters (UCs) and minimizing the incidence of CAUTIs in the internal medicine department of a university hospital. Methods: A multi-modal intervention was developed, including training sessions, urinary catheterization reminders, surveillance systems, and mechanisms for staff feedback of results. The frequency of UC use and incidence of CAUTIs were recorded in three-month periods before (P1) and during the intervention (P2). Findings: The catheterization rate decreased significantly during P2 [27.8% vs 16.9%; relative risk (RR): 0.61; 95% confidence interval (CI): 0.57–0.65]. We also observed a reduction in CAUTI risk (18.3 vs 9.8%; RR: 0.53; 95% CI: 0.30–0.93), a reduction in the CAUTI rate per 1000 patient-days [5.5 vs 2.8; incidence ratio (IR): 0.52; 95% CI: 0.28–0.94], and a non-significant decrease in the CAUTI rate per 1000 catheter-days (19.3 vs 16.9; IR: 0.85; 95% CI: 0.46–1.55). Conclusion: The multi-modal intervention was effective in reducing the catheterization rate and the frequency of CAUTIs.